Screening of Amylolytic Bacteria from the Intestines of Tilapia (Oreochromis niloticus) Cultivated in Rice Fish Farming in Panembangan Village, Cilongok District, Banyumas - salsa nabila; Kasprijo; Rima Oktavia Kusuma; Sri Marnani; Muhammad Ikhwan Ihtifazhuddin (PT. Artha GenetikaLab Indonesia, 2025)
Amylolytic bacteria in the digestive tract of tilapia are bacteria that produceamylase enzymes, which function to break down carbohydrates, thereby aidingthe digestive process. The presence of amylolytic bacteria is influenced by feedand the environment. The purpose of this study was to determine the proportionand activity index of amylolytic bacteria in the intestines of tilapia. This studyused an observational method with purposive sampling. Amylolytic bacteriawere isolated from the intestines of tilapia in Rice fish farming Blocks A and E.The successfully isolated bacteria were grown on 1% starch agar medium withan incubation time of 48 hours and observed at 24-hour intervals. Then, severalcharacteristic tests were carried out, including Gram staining, KOH, catalase,and oxidase tests. Based on the results of the study, the proportion of amylolyticbacteria was found in 10 isolates with a proportion of 44% and 12 isolates witha proportion of 48% in the intestines of tilapia from the two blocks. The averageamylolytic activity index obtained from block A was 0.96 ± 0.237, and fromblock E was 1.49 ± 0.501. The largest amylolytic activity index was obtainedin isolate KSA 19 with a value of 1.33 from block A, while from block E, thelargest amylolytic activity index value was 2.6 in isolate KSE 5.